2022
DOI: 10.1101/2022.10.11.22280965
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Monkeypox vaccination willingness, determinants, and communication needs in gay, bisexual, and other men who have sex with men, in the context of limited vaccine availability in the Netherlands (Dutch MPX-survey)

Abstract: Introduction. In the global monkeypox outbreak primary preventive vaccination is offered to people at higher risk for infection. We study vaccine acceptance and its determinants, to target and tailor public health (communication-)strategies in the context of limited vaccine supply in the Netherlands. Methods. Online survey in a convenience sample of gay, bisexual and other men who have sex with men, including transgender persons (22/07-05/09/2022, the Netherlands). We assessed determinants (sociodemographic, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…On the Hornet app, users received an inbox message with the link of the survey, which had an overall click-through rate of 15.1% during the 30 July–12 August period. Data related to the Netherlands were collected through a web survey on other platforms according to the same protocol [ 3 ] albeit with a few questions from the app-based survey omitted (see second table’s footnote).…”
Section: Survey and Participantsmentioning
confidence: 99%
“…On the Hornet app, users received an inbox message with the link of the survey, which had an overall click-through rate of 15.1% during the 30 July–12 August period. Data related to the Netherlands were collected through a web survey on other platforms according to the same protocol [ 3 ] albeit with a few questions from the app-based survey omitted (see second table’s footnote).…”
Section: Survey and Participantsmentioning
confidence: 99%
“…We conducted an online survey in mpox unvaccinated GBMSM/TGP, around the start of the mpox PPV-program in the Netherlands ( 16 ). The survey evaluates willingness to accept PPV and its determinants, and it also asked persons for their recommendations in campaigning and PPV-program procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we thank all participants for contributing with their invaluable comments and responses. This work is available as Preprint: Dukers-Muijrers et al ( 16 ).…”
mentioning
confidence: 99%
“…They found that 70-85% of GBMSM in July-September 2022 were willing to accept mpox vaccination. 32,33 The perceived sense of urgency may have been low at the time people were invited for PPV, especially for the second dose, as the outbreak was already declining. This may have led to a lower vaccine uptake and vaccination coverage than expected.…”
Section: Discussionmentioning
confidence: 99%